Fuzheng Huayu Recipe and its active compounds inhibited HBeAg production by promoting TOMM34 gene expression in HBV-infected hepatocytes - Xing, Lu; Zeng, Rui; Huang, Kai; Xue, Jingbo; Liu, Hongliang; Zhao, Zhimin; Peng, Yuan; Hu, Xudong; Liu, Chenghai (Frontiers in Pharmacology, 2022)
Background and aim: Fuzheng Huayu Recipe (FZHY) is a Chinese patent medicine (approval No.: Z20020074) included in the national medical insurance catalogue, which is mainly used for anti-hepatic fibrosis treatment of hepatitis B virus (HBV) induced liver fibrosis and liver cirrhosis. In clinical practice, we discovered that FZHY might also have a direct anti-HBV effect on inhibiting HBeAg production, but the mechanism underlying was unclear. This study aimed to clarify the molecular mechanism of the inhibition effect of FZHY on HBeAg production. Methods: The decrease degree of serum HBeAg titer in FZHY+ entecavir (ETV) group patients were analyzed through clinical data. C57BL/6N-Tg (1.28HBV) /Vst HBV transgenic mice were used for in vivo experiments. HepG2. 2.15 cells (wild-type HBV replication cells) were used for in vitro experiments. Results: The clinical study results showed that the decrease degree of serum HBeAg titer in FZHY+ETV group was significantly higher than that in ETV group after 48 weeks treatment. In vivo experiments results showed that FZHY could significantly reduce the serum HBeAg titer in HBV transgenic mice, and promote HBeAg seroconversion. In vitro experiments results showed that FZHY could reduce HBeAg titer dependently, but it did not significantly inhibit the expression of HBsAg and HBV-DNA. Further cell experiments in vitro discovered that TOMM34 might be the key target for FZHY to inhibit HBeAg production. The subsequent pharmacological screening experiment of 20 active compounds in FZHY showed that quercetin, baicalin and cordycepin could promote the expression of TOMM34 gene and reduce the production of HBeAg. Conclusions: In conclusion, FZHY and its active compounds quercetin, baicalin and cordycepin could inhibit HBeAg production by promoting the expression of TOMM34 gene in HBV-infected hepatocytes.